Evaluation of pesticide spraying quality in wetland rice cultivation in Malaysia - Ahmed, Modather Mairghany Abdin; Yahya, Azmi; Adam, Nor Mariah; Mat Su, Ahmad Suhaizi; Elsoragaby, Suha Gaafar Babekir (Malaysian Society of Agricultural Engineers, 2019)
The uniformity spray distributions, and labour quality of work were analysed for various operating conditions for two real field operations in wetland rice cultivation in Malaysia. Water sensitive papers used as positioned targets closed to the plant and were compared against known and standard coverage, droplet size spectra and class size distribution verified through manual counting. The results indicate that commonly used nozzle, swath width, nozzle heights, nozzle direction, pressures and labour performance often affect the operation quality and spraying distribution. The result showed that the spraying penetration index of 32.13%, which is 67.87% lesser than the desired penetration ratio. Spray applications distribution showed droplet density between 14 and 108 drops cm2 and a wide range of droplet size spectra. The study shows significant difference in distribution in the field. The higher distribution of very fine droplet (75 - 108 droplet/cm2) was mainly in the area of 0 to 1 metre from 4 edges of the field and 1m left and right the 8 working line, then (61 - 73 droplets cm2) and this in the location 1 to 2 m right and left the working line, the other areas ranges from (14 - 60 droplets cm2). The result shows there are 3.3% is uncovered horizontal area due to labour performance. Most of the operator 71.43% have speed higher than the ideal speed while 28.57% of the operator have speed lower than the idea. 34% of farmers have applied medium sprays, 66% of them have applied finer sprays.